2023
DOI: 10.3390/ma16083181
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Microstructural Studies on the Machining of Inconel 600 in WEDM Using Untreated and Cryogenically Treated Zinc Electrodes

Abstract: Any industry that manufactures dies, punches, molds, and machine components from difficult-to-cut materials, such as Inconel, titanium, and other super alloys, largely relies on wire electrical discharge machining (WEDM). In the current study, the effect of the WEDM process parameters on Inconel 600 alloy with untreated zinc and cryogenically treated zinc electrodes was investigated. The controllable parameters included the current (IP), pulse-on time (Ton), and pulse-off time (Toff), whereas the wire diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…This analysis was applied to the results of all the recorded data, both for the recorded values of the parameters of the roughness of the machined surface Ra, as well as for the recorded values of the performance parameter of the electrical discharge process MRR. In the case of the recorded data where the presence of outliers or extreme values was confirmed, based on the analysis, and it was not possible to establish a normal distribution, even in cases where the normality of the distribution of the data was not proven even after the exclusion of the confirmed outliers, exponential and Box–Cox transformations were performed, which ensured the correctness of the statistical analysis of experimentally measured values of monitored output-dependent parameters Ra and MRR in micro-WEDM of HSS [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…This analysis was applied to the results of all the recorded data, both for the recorded values of the parameters of the roughness of the machined surface Ra, as well as for the recorded values of the performance parameter of the electrical discharge process MRR. In the case of the recorded data where the presence of outliers or extreme values was confirmed, based on the analysis, and it was not possible to establish a normal distribution, even in cases where the normality of the distribution of the data was not proven even after the exclusion of the confirmed outliers, exponential and Box–Cox transformations were performed, which ensured the correctness of the statistical analysis of experimentally measured values of monitored output-dependent parameters Ra and MRR in micro-WEDM of HSS [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ANOVA approach was employed to determine the contribution made by all of the input parameters and errors in the discrepancy of answers. The user can then focus on the significant element that is most probable to lead to an alteration in the responses by assessing the role of the parameters in the changed responses and the impact of single parameters on the response variation [27].…”
Section: Literature Surveymentioning
confidence: 99%
“…On the basis of an analysis of the current state of the given issue, it can be concluded that several relevant experimental studies have been carried out to date, the aim of which was to contribute to the improvement of the quality of machined surfaces after EDM with a wire electrode in terms of dimensional and geometric accuracy and precise surface quality in terms of roughness parameters from the point of view of low thermal impact on surface and subsurface layers [11][12][13]. These experiments were performed from different points of view.…”
Section: Introductionmentioning
confidence: 99%